Punctuation in late Middle English Medical Writing: Constantinus Africanus’ Venerabilis Anatomia in London, Wellcome Library, MS Wellcome 290 (ff. 1r-41v) - Romero-Barranco, Jesús (My University, 2015)
Within the field of Palaeography, punctuation could be defined as the most rudimentary aspect, as it took an extremely long time to evolve. By the 13th century, the punctus and the inverted semicolon were the most widespread marks of punctuation in England, and it was not until the end of the 16th century that the whole inventory of contemporary punctuation marks fully developed (Petti 1977: 25). Notwithstanding the recent apparoaches to the study of historical punctuation (Alonso-Almeida 2001: 207; Calle-Martín and Miranda-García 2005: 95; Calle-Martín and Miranda-García 2007: 357-58), historical punctuation has been traditionally neglected by the academia in the assumption that it was meaningless and haphazard (Denholm-Young 1954: 77; Hector 1958: 45). The present study analyses the punctuation system found in a late Middle English anatomical treatise, Constantinus Africanus Venerabilis’ Anatomia, housed in London, Wellcome Library, MS Wellcome 290 (ff. 1r-41v). This paper is conceived with a threefold objective: a) to offer a description of the different uses and functions of punctuation symbols; b) to determine whether the scribe employed rhetoric or grammatical punctuation; and c) to offer the set of contemporary punctuation marks that would perform those functions nowadays. On methodological grounds, this research stems from the Málaga Corpus of Late Middle English Scientific Prose (http://hunter.uma.es), which contains a collection of hitherto unedited late Middle English Fachprosa displaying the lemma, word-class, accidence and meaning of every running word in the corpus, punctuation marks also included. The tool Text Search Engine (Miranda-García and Garrido-Garrido 2013) has then facilitated the automatic generation of the complete inventory of punctuation marks in the text, including the context and folio in which they occur.
Keywords: Inglés - Historia; Paleografía; Lingüística Histórica; Codicología; Lingüística del corpus